THE INFLUENCE OF SOME BANK FINANCIAL RATIOS CHARACTERISTICS ON PROFITABILITY IN SHARIA BANK - Sri Murtiningsih; Achmad Tohirin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research seeks to analyze financial ratios in Islamic Commercial Banks (BUS) and Islamic Business Units (UUS). This research uses several variables from financial ratios to support the research. The variable indicators of financial ratios are Capital Adequacy Ratio (CAR), Financing to Debt Ratio (FDR), Non Performing Financing (NPF), Operating Costs to Operating Income (BOPO), and Third Party Funds (DPK) with the observation period from 2015 to 2020. This research analysis method applies Autoregressive Distributed Lag (ARDL) with the data type, namely time series data. The findings of this research show that in Islamic Commercial Banks (BUS) the CAR, FDR, NPF, BOPO, and DPK variables in the short term have an influence on bank profitability, namely ROA and ROE. In the long term the CAR variable only has an effect on ROE, the FDR and BOPO variables have an influence on ROA and ROE. Meanwhile, the NPF and DPK variables only influence ROA. Subsequent research findings in Islamic Business Units (BUS) show that CAR, FDR, NPF, BOPO, and DPK variables in the short term have an impact on bank profitability, namely ROA and ROE. In the long run, only the FDR variable has no effect on ROA, whereas in ROE only BOPO has an effect. Keywords: Banking Profitability and Banking Financial Ratios.